Evaluation of Serum IL-41 as a Potential Biomarker in a Group of Iraqi Patients with Rheumatoid Arthritis - Tawfeeq, Ayat F.; AL-Hadithi, Hayfaa S.; Gorial, Faiq I. (Journal of the Faculty of Medicine Baghdad, 2025)
Background: Most individuals with inflammatory arthritis are diagnosed with rheumatoid arthritis (RA), which is an immunological disorder characterized by the development of autoantibodies, particularly anti-cyclic citrullinated peptide (ACCP) antibodies, which play a significant role in initiating inflammatory responses. Recent studies have shown that the production of cytokines contributes to the progression and dissemination of RA. Objectives: To assess the predictive capability of Interleukin 41 (IL-41) compared with ACCP and its correlation with disease activity and treatment response in a group of Iraqi patients afflicted with RA. Methods: One hundred patients with RA and fifty healthy controls constituted the total number of participants in this case-control study. The research was conducted in Baghdad Teaching Hospital from November 2023 to February 2024. The American College of Rheumatology 2010 criteria were used for patient recruitment. In order to evaluate the role of the biomarkers, an enzyme-linked immunoassay (ELISA) technique was used. Results: The level of IL-41 in RA patients (5.2 ± 2.65 ng/mL) was significantly higher than in healthy controls (3.0 ± 1.43 ng/mL). The mean serum IL-41 concentration was highest in the severe form (6.8 ± 2.91 ng/mL), followed by moderate and low disease activity. A positive correlation was also detected between the serum IL-41 level and the ACCP. Serum IL-41 was significantly higher among patients taking methotrexate (5.8 ± 3.30 ng/mL), more than both etanercept (5.1 ± 2.47 ng/mL) and etanercept + methotrexate (4.6 ± 1.82 ng/mL). Conclusion: Elevated concentrations of IL-41 in the serum of RA patients, potentially serve as diagnostic markers for RA. It helps as an indicator for the disease activity and therapeutic response.